Multiple Professional Institutes’ Scene and Corporate Rescue Work-Related Professionalism - Onesmus Ayaya (SAGE Open)
The study explored corporate rescue professionalism in a setting with multiple professional institutes. The study employed qualitative inquiry processes to gather and explore field data. Among others, interviews and document content analysis were employed to document the indicators of professionalism in multiple professional institutes’ scenes. The collected data were examined qualitatively, employing triangulation and thematic analysis and supplying complementary explanations to the developing results. The results show that work-related professionalism cannot be uniformly constructed in a setting with multiple professional institutes. Professionalism requires an occupation-specific learning and development regime. An exclusive selling proposition is hard to craft in a setting with multiple professional institutes and requires a qualification framework that values regulated practices in corporate laws and regulations. The short learning and development programmes are inconsistent with skills development laws calling for competency-based learning and development. Competency-based learning and development in the investigated case require higher educational programmes to be enrolled on the national qualifications framework administered by the relevant regulatory agency. The results’ practical implications suggest that the regulator will need to lead an occupation-specific qualification development process to permit corporate rescue practitioners to embrace a uniform socialisation structure with shared values that are needed to entrench occupational professionalism. The process will require documentation of regulated corporate rescue practices.